2022
DOI: 10.32604/cmc.2022.022161
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Deep Learning Model for Plant Disease Detection Using Particle Swarm Optimizer

Abstract: Plant diseases are a major impendence to food security, and due to a lack of key infrastructure in many regions of the world, quick identification is still challenging. Harvest losses owing to illnesses are a severe problem for both large farming structures and rural communities, motivating our mission. Because of the large range of diseases, identifying and classifying diseases with human eyes is not only time-consuming and labor intensive, but also prone to being mistaken with a high error rate. Deep learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…AlexNet [ 35 ] is made up of eight layers, five of which are convolutional and three of which are completely connected. Each convolutional layer is paired with a maxpooling layer and a normalization layer to reduce the image size and normalize the output pixel values [ 36 ]. For AlexNet, the images are resized to 224 ∗ 224 pixels.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…AlexNet [ 35 ] is made up of eight layers, five of which are convolutional and three of which are completely connected. Each convolutional layer is paired with a maxpooling layer and a normalization layer to reduce the image size and normalize the output pixel values [ 36 ]. For AlexNet, the images are resized to 224 ∗ 224 pixels.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…CNNs and recurrent neural networks (RNN) are the most common deep learning models [ 40 ]. Their variations make up the majority of existing deep-learning models.…”
Section: Cnn’s Model Setting and Phasesmentioning
confidence: 99%
“…Nonetheless, it faces numerous obstacles, such as a complicated background , a high degree of similarity, and the segmentation of regions. [1][2][3]There are two types of methods for identifying crop diseases and pests. Elaraby et al [1] suggested a deep-learning technique for recognising 25 distinct plant diseases.…”
Section: Literature Surveymentioning
confidence: 99%
“…Manual experience is required, and the procedure is time-consuming and labor-intensive. Due to the wide variety of pests and unequal distribution of disease spots, it is challenging for specialists to undertake timely and accurate screening [1][2][3]. Consequently, precise disease severity estimation aids in wheat disease control and prevention.…”
Section: Introductionmentioning
confidence: 99%